The content and procedure for maintaining the state cadastre of flora objects in the unified system of state cadastres - Shakhzod Sattorov Yarashovich; Temurbek Ismatov Akbar o’g’li (Genius Journals, 2025)
The Unified System of State Cadastres contains information on the content and procedure for maintaining the state cadastre of plant world objects.
Keywords: Cadastre; plant world; content; essence